EXPLORING A DIGITAL TOOL “NEARPOD” TO IMPROVE STUDENTS’ SKILL IN WRITING - Puji Lestari; Lambok Hermanto Sihombing (EDUPEDIA, 2022)
Teachers with new and innovative methods will make teaching more engaging. The students will not get bored easily as they get enjoyable atmosphere. In this study, the researchers aim to elaborate the use of Nearpod as a digital tool to improve students’ skills. There are lots of skills that students can enhance through Nearpod. However, in this study, the researchers focus on how Nearpod can be utilized as a digital platform to improve their writing skill. To support this analysis, the researchers applied a qualitative methodology and used the Teaching by Principle theory by H. Douglas Brown and Heekyong Lee. The data was taken from official website of Nearpod, www.nearpod.com and some supporting articles. The result showed that Nearpod could be used as one of effective digital tools to enhance students’ skill in writing.